2017
DOI: 10.1002/ajh.24774
|View full text |Cite
|
Sign up to set email alerts
|

The BCR‐ABL1 transcript type influences response and outcome inPhiladelphia chromosome‐positive chronic myeloid leukemia patients treated frontline with imatinib

Abstract: Funding information BolognAIL, AIRCThe most frequent BCR-ABL1 fusion transcripts in chronic myeloid leukemia (CML) are the e13a2 (b2a2) and the e14a2 (b3a2) ones. In the imatinib era few studies addressing the prognostic significance of the BCR-ABL1 transcript type in early chronic phase CML have been published. Overall, these studies suggest that in e14a2 patients the response to imatinib is faster and deeper. To evaluate if the BCR-ABL1 transcript type (e13a2 compared to e14a2) affect the response to imatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
123
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 83 publications
(131 citation statements)
references
References 45 publications
6
123
1
1
Order By: Relevance
“…Bennour et al found that patients with the e14a2 transcript type were significantly older than patients in the e13a2 group (mean age of 56 years vs 26 years; P = .001). Other studies did not find a correlation between age and transcript types …”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Bennour et al found that patients with the e14a2 transcript type were significantly older than patients in the e13a2 group (mean age of 56 years vs 26 years; P = .001). Other studies did not find a correlation between age and transcript types …”
Section: Introductionmentioning
confidence: 79%
“…Many studies found no association between leukocyte counts and hemoglobin levels at the time of diagnosis and the transcript types . However, in their study, the German investigators demonstrated that patients with the e13a2 transcript had significantly higher baseline median leukocyte counts compared with patients with the e14a2 transcript (88 × 10 9 /L vs 65 × 10 9 /L; P <.001), but no such relationship was shown for hemoglobin levels .…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations